2020
DOI: 10.15173/ijsap.v4i2.4237
|View full text |Cite
|
Sign up to set email alerts
|

Students as partners in collaborative course design and educational research

Abstract: The impact of collaborative course design is explored in this qualitative, longitudinal study of an upper-year course in which 30-40 undergraduate students co-designed the course syllabus, including both course content and assessments. In addition, the research questions and methods were co-designed by a research team involving six undergraduate student partners, an educational developer, and two faculty members. Student written work and focus-group transcripts were coded and analyzed using longitudinal interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…For example, in terms of how our experiences working together might impact our future or personal goals, Brad and Alice (staff and faculty) focused on their future work with student partners and how they might do things differently, whereas Emily and Christopher (student partners) focused more on their personal and professional development. 48 who collaborate on course development projects (e.g., Hanna-Benson et al, 2020;Kaur et al, 2019), the student partners in this study indicated that they gained new skill sets by collaborating on the course redesign and that they felt valued by way of contributing to the project with a clear purpose. Additionally, the instructor and instructional designer also benefited from this partnership through their reflections on effective mentorship and reconceptualization of roles to enhance the degree of inclusion of students as partners in future course redesign projects.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, in terms of how our experiences working together might impact our future or personal goals, Brad and Alice (staff and faculty) focused on their future work with student partners and how they might do things differently, whereas Emily and Christopher (student partners) focused more on their personal and professional development. 48 who collaborate on course development projects (e.g., Hanna-Benson et al, 2020;Kaur et al, 2019), the student partners in this study indicated that they gained new skill sets by collaborating on the course redesign and that they felt valued by way of contributing to the project with a clear purpose. Additionally, the instructor and instructional designer also benefited from this partnership through their reflections on effective mentorship and reconceptualization of roles to enhance the degree of inclusion of students as partners in future course redesign projects.…”
Section: Discussionmentioning
confidence: 77%
“…"Students as partners" is a concept that situates students as co-creators of knowledge in partnership with instructors, and it reflects how students can collaborate in activities involving teaching and learning (Healey et al, 2014). Past studies have documented various ways in which students, instructors, and staff can collaborate through partnerships in the scholarship of teaching and learning (e.g., Popovic et al, 2021) and curriculum design (e.g., Hanna-Benson et al, 2020;Lubicz-Nawrocka, 2018). Regarding curriculum design, students have helped to adapt or refine the syllabus after the course has started (e.g., Hess, 2008;Moreno-Lopez, 2005) and contributed to creating assessments (Hudd, 2003) and assessment policies (Moreno-Lopez, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meaningful partnerships, involvement, and discourse provide opportunities to identify and address alienating practices from multiple viewpoints to support more equitable and inclusive educational and institutional practices (Gibson & Cook-Sather, 2020). Student partnerships can meaningfully transform curriculum design, including learning objectives, assessments, course content, and learning activities, and program review (Hanna-Benson et al, 2020; McKenny & Anderson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy to encourage independence is to collaboratively plan assignments, course structure, and norms with students (Hanna-Benson, 2020). Course assessments designed through students’ submission of sample test questions over the course of the semester is one option.…”
Section: Strategies For Instructors To Design Inclusive Learning Expe...mentioning
confidence: 99%